Role of Lipid Nanoparticles in COVID-19 in Repurposing Drugs and Vaccines - Basnet, Rajesh; Basnet, Til B.; Basnet, Buddha Bahadur; Khadka, Sandhya; Sapkota, Sanjeep (Current Nanoscience, 2022)
Background: The spread of new coronavirus 2019, the causative agent of viral pneumonia documented in Wuhan, brought a recent public health crisis globally. The best solution to overcome this pandemic is developing suitable and effective vaccines and therapeutics. However, discovering and creating a new drug is a lengthy process requiring rigorous testing and validation. Objective: Despite many newly discovered and old repurposed COVID-19 drugs under clinical trial, more emphasis should be given to research on COVID-19 NPs-based medicines, which could improve the efficacy of antiviral drugs to reduce their side effects. The use of NPs as carriers can reduce the frequency and duration of drug ingestion, enhance approved antiviral therapeutics' effectiveness, and overcome their limitations, such as low bioavailability. Besides, they can play a crucial role in fighting against the COVID-19 pandemic. In this regard, nanotechnology provides opportunities to develop new strategies for preventing, diagnosing, and treating COVID-19. Conclusion: This review highlighted the importance of NMs-based technical solutions in antiviral drugs for testing against the SARS-CoV-2 virus emergencies in the form of nanotherapeutics.
Keywords: nanotherapy